2012
DOI: 10.3389/fgene.2012.00252
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-mediated deregulation in leukemia

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs 18–25 nucleotides (nt) long able to fine-tune post-transcriptional gene expression. Extensive investigation into biogenesis, mechanism of action and functions of miRNAs has clearly revealed their prompt control in developmental timing, differentiation, proliferation, cell death, and metabolism. Deregulation of miRNA-mediated pathways may contribute to pathological conditions such as tumors, including hematological cancers, thus suggesting that miRNAs act both as tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 107 publications
0
6
0
1
Order By: Relevance
“…A global imbalance of miRNA expression (and function) was reported in both solid and hematological malignancies 4 including acute myeloid leukemia (AML). 5 AML includes genetically diverse malignancies characterized by frequent chromosome translocations and variable response to treatment. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…A global imbalance of miRNA expression (and function) was reported in both solid and hematological malignancies 4 including acute myeloid leukemia (AML). 5 AML includes genetically diverse malignancies characterized by frequent chromosome translocations and variable response to treatment. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…miRNA possesses diverse roles that up- or down-regulate target gene expression [ 52 - 57 ]. To identify the miR-130a target genes responsible for its effects on cervical cancer cells, we used bioinformatics and functional knowledge associated with NF-κB and miR-130a and chose TNF-α as a candidate gene for further study.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs, miR‐s) are a class of endogenous small, non‐coding RNAs with a length of 22–23 nt RNAs, and could regulate expression of hundreds of target mRNAs simultaneously in a post‐transcriptional manner, thus modulating a variety of cell functions including cell proliferation, differentiation, death, tumor development and also radiosensitivity [Hao et al, ; Liu et al, ; Lin et al, ]. It was also reported that miRNAs might function as tumor suppressor genes and oncogenes [D'Amato et al, ; Dell'aversana and Altucci, ]. For example, dysregulation of the miR‐17‐92 cluster can induce B cell lymphoma while the expressing level of let‐7 is associated with tumor progression and poor prognosis of lung cancer patients [Wang and Lee, ; John‐Aryankalayil et al, ; Shu et al, ; Tian et al, ].…”
mentioning
confidence: 99%